Mighty Dwarfs: Arabidopsis Autoimmune Mutants and Their Usages in Genetic Dissection of Plant Immunity - van Wersch, Rowan; Li, Xin; Zhang, Yuelin (Frontiers in Plant Science, 2016)
Plants lack the adaptive immune system possessed by mammals. Instead they rely on innate immunity to defend against pathogen attacks. Genomes of higher plants encode a large number of plant immune receptors belonging to different protein families, which are involved in the detection of pathogens and activation of downstream defense pathways. Plant immunity is tightly controlled to avoid activation of defense responses in the absence of pathogens, as failure to do so can lead to autoimmunity that compromises plant growth and development. Many autoimmune mutants have been reported, most of which are associated with dwarfism and often spontaneous cell death. In this review, we summarize previously reported Arabidopsis autoimmune mutants, categorizing them based on their functional groups. We also discuss how their obvious morphological phenotypes make them ideal tools for epistatic analysis and suppressor screens, and summarize genetic screens that have been carried out in various autoimmune mutant backgrounds.